The Investigation of the Viewpoint of Academic Staff and Graduate Students in Teaching Geometry in Elementary School - Bayrak, Nurten; Yuce, Salim; Yuce, Muzaffer Kaan (ELSEVIER SCIENCE BV, 2014)
Determination of the viewpoint of academic staff and graduate students in teaching geometry, which is an essential component of mathematics, has great importance. From this point of view, the aim of this study is to investigate views of academic staff and graduate students on methods such as technology, material, projects, teaching of arithmetic, abstraction and problem-solving in the teaching of geometry. The study was carried out on a total of 46 mathematicians, ranging from graduate students to professors. In order to describe the current situation, a screening model was used. A working group was asked 15 open ended questions to determine their views. Descriptive statistics of the analyzed data collected (arithmetic mean, standard deviation) were used. In addition to this, comparisons were made and the results were interpreted. Suggestions have been made on the basis of the data obtained at the end of the research. (C) 2013 The Authors. Published by Elsevier Ltd. Selection and/or peer-review under responsibility of Academic World Education and Research Center.
Keywords: Academic Staff; Graduate Students; Screening Model; Education & Educational Research